(untitled) (Research, Society and Development, 2023)
To analyze the vaccination profile against poliomyelitis in the Northeast between 2017 and 2022. It consists of a descriptive epidemiological study carried out using data collected at the Department of Informatics of the Unified Health System (DATASUS). The variables analyzed were the number of vaccine doses applied in the analyzed period according to age, year, type of immunobiological and state, in addition to evaluating the vaccination coverage rate in the region. The collected data were tabulated and stored in the Microsoft Office Excel® program for later availability in absolute and relative frequencies of the results. 19,158,387 doses of polio vaccine were administered, with a constant number of doses applied in each year analyzed, with the exception of 2021 in which there was a drop in vaccination compared to the previous year of 13.89% and with the following year of 17.16%. The highest number of doses applied was VIP, corresponding to 65% of vaccines, while 35% were VOP. Vaccination coverage in the Northeast during the evaluated period was 65.82%, with Ceará presenting the highest coverage rate with 78.44%, followed by Alagoas and Sergipe with, respectively, 70.8% and 70.3%. There was a decrease in the number of vaccines applied against poliomyelitis between 2017 and 2022, and the vaccine coverage goal was not achieved in any of the years analyzed. Therefore, there is a risk of imminent reintroduction and circulation of the wild virus.